'So Kuoↄ Kye Bϵ Yi': disrupting constructions of masculinities among the Dagaaba of Northwestern Ghana. Issue 1 (2nd January 2021) - Dery, Isaac; Apusigah, Agnes Atia
ABSTRACT: In this article, our aim is to present an African-centered framework on how researchers interested in critical studies on African men and masculinities might think through and think from Africa in ways that might privilege a more nuanced reading and examining of gendered subjectivities in Africa. Drawing on interviews with young men in northwestern Ghana, this article offers an understanding of how young Dagaaba men and their masculinities could be better understood in relation to an emerging neoliberal rural culture. Young men in this study acknowledge the possibility of negotiating expressions of masculinities which are more progressive, while simultaneously remaining heavily invested in retaining certain behaviors, practices, and patriarchal structures which legitimize the currency of traditionally hegemonic masculinities. The article concludes that attempts seeking to deconstruct hegemonic masculinities must, first and foremost, appreciate the shifts and complexities of masculinities and the discursive materiality of acts of violence over time and space.